Acid-Base Status Disturbances in Patients on Chronic Hemodialysis at High Altitudes - Javier Enrique Cely; Oscar G. Rocha; María J. Vargas; Rafael M. Sanabria; Leyder Corzo; Roberto E. D'Achiardi; Eduardo A. Zúñiga (International Journal of Nephrology)
Background. Acid-base disorders have been previously described in patients with chronic hemodialysis, with metabolic acidosis being the most important of them; however, little is known about the potential changes in acid-base status of patients on dialysis living at high altitudes. Methods. Cross-sectional study including 93 patients receiving chronic hemodialysis on alternate days and living in Bogotá, Colombia, at an elevation of 2,640 meters (8,661 feet) over sea level (m.o.s.l.). Measurements of pH, PaCO2, HCO3, PO2, and base excess were made on blood samples taken from the arteriovenous fistula (AVF) during the pre- and postdialysis periods in the midweek hemodialysis session. Normal values for the altitude of Bogotá were taken into consideration for the interpretation of the arterial blood gases. Results. 43% (n= 40) of patients showed predialysis normal acid-base status. The most common acid-base disorder in predialysis period was metabolic alkalosis with chronic hydrogen ion deficiency in 19,3% (n=18). Only 9,7% (n=9) had predialysis metabolic acidosis. When comparing pre- and postdialysis blood gas analysis, higher postdialysis levels of pH (7,41 versus 7,50, p<0,01), bicarbonate (21,7mmol/L versus 25,4mmol/L, p<0,01), and base excess (-2,8 versus 2,4, p<0,01) were reported, with lower levels of partial pressure of carbon dioxide (34,9 mmHg versus 32,5 mmHg, p<0,01). Conclusion. At an elevation of 2,640 m.o.s.l., a large percentage of patients are in normal acid-base status prior to the dialysis session (“predialysis period”). Metabolic alkalosis is more common than metabolic acidosis in the predialysis period when compared to previous studies. Paradoxically, despite postdialysis metabolic alkalosis, PaCO2 levels are lower than those found in the predialysis period.